2021
DOI: 10.3390/en14196134
|View full text |Cite
|
Sign up to set email alerts
|

Research on Energy Management Method of Plug-In Hybrid Electric Vehicle Based on Travel Characteristic Prediction

Abstract: In the research on energy management methods of plug-in hybrid electric vehicles, it is expected that a future trend will be to optimize energy management using the information provided by the global positioning system (GPS) and intelligent transportation system (ITS), which is relatively scarce in current research. This study proposes a PHEV energy management method based on travel characteristic prediction. Firstly, this study processes the historical travel data of a certain driver obtained by GPS and ITS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have shown that vehicle energy consumption is sensitive to driving cycles [6,7]. In view of this hot topic, we have studied the characteristic relationship between energy consumption and the driving cycles of plug-in hybrid electric vehicles (PHEVs) [8,9]. Chlopek et al, based on the energy consumption test data of battery electric vehicles (BEVs) and conventional ICEVs, analyzed the average speed and the average absolute value of the product of speed and acceleration, which were the best characteristics to describe vehicle energy consumption [10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies have shown that vehicle energy consumption is sensitive to driving cycles [6,7]. In view of this hot topic, we have studied the characteristic relationship between energy consumption and the driving cycles of plug-in hybrid electric vehicles (PHEVs) [8,9]. Chlopek et al, based on the energy consumption test data of battery electric vehicles (BEVs) and conventional ICEVs, analyzed the average speed and the average absolute value of the product of speed and acceleration, which were the best characteristics to describe vehicle energy consumption [10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies have shown that driving cycle information can make a difference in vehicle energy management [12][13][14]. In view of this hot topic, we have studied the characteristic relationship between energy management and the driving cycle of PHEV [15]. Driving cycle information discussed in this paper indicates the vehicle speed trajectory, which is an indication of vehicle speed versus sample time [16,17].…”
Section: Introduction 1motivationsmentioning
confidence: 99%
“…Then, the historical data on car driving is characterized, and the collected data is identified and classified, taking into account traffic information. The SOC algorithm plans the driving trajectory, and finally, the previously obtained data is managed using the A-ECMS energy management method [24]. Santos, N. D. L. et al investigated the effect of changes in facial expressions of suspects on the prediction of idiosyncratic diagnostic recognition to provide public safety personnel with a characteristic image of the suspect.…”
Section: Introductionmentioning
confidence: 99%